Competence-based VET in the Netherlands : background and pitfalls - Biemans, Harm J. A. [Verfasser]; Nieuwenhuis, Loek F. M. [Verfasser]; Poell, Rob [Verfasser]; Mulder, Martin [Verfasser]; Wesselink, Renate [Verfasser] (My University, 2004)
"In the Dutch Vocational Education and Training (VET) system, competence-based education is the leading paradigm for innovation, both at the system level and at the level of learning environments. This article provides an historical analysis of the development of competence-based education in various countries and explores the concept of competence and its popularity. Possible pitfalls with respect to the concept of competence, standardisation, school and workplace learning, determining learning activities, assessment of competencies, changing teacher roles/identity and competence-based management will be discussed. Taking these pitfalls into account, roads for future development will be sketched. A learning policy connecting governance, practice and research is believed to be the most fruitful way to develop flexible VET systems that are suited to the emerging knowledge-based economy." (Autorenreferat, BIBB-Doku)
Keywords: L 6.2.1 Standards/Gütekriterien; L 1.3 Curriculumentwicklung; L 6.3.1 Diagnose- & Messinstrumente; T 1.5 International vergleichende Berufsbildungsforschung; I 2.2.1 Westeuropa; Berufsbildung; Kompetenzorientierung; Curriculumentwicklung; Kompetenzforschung; Internationaler Vergleich; Niederlande